Apis cerana F. as an Important Natural Pollinator of Radish (Raphanus sativus L.) under Mid-hill Conditions of Himachal Pradesh - Sharma, Harish Kumar; Katna, Sapna; Rana, B. S.; Rana, Kiran (International Journal of Bio-resource and Stress Management, 2016)
The present studies were undertaken to find out the pollination efficiency of Apis mellifera L. and other natural pollinators in radish (cv. Pusa Himani) and their impact on yield and quality of seeds under mid hill conditions of Himachal Pradesh. A. cerana was dominant amongst all insect visitors being 5.85 and 6.6 bees m-2 5 minutes-1 in 2011 and 2012, respectively. A. mellifera (introduced bee species) population was quite low (0.3) during 2011 which clearly indicated that the bees did not get conditioned to the target crop. Pollination index showed that A. cerana scored maximum i.e. 13.63 and 15.38 in 2011 and 2012, respectively. Pod set recorded during 2011 and 2012 in radish did not vary significantly at different distances from the A. mellifera colonies. The values being 34.42, 28.55, 30.9 and 29.3% respectively at 25 m, 50 m, 75 m and 100 m distance in 2011. The respective values during 2012 were 28.17, 27.09, 25.81 and 22.73%. During 2012, the parameters of seed quality like pod set, seed number and seed weight showed decreasing trend with increase in the distance from the placement of A. mellifera colony. This could be due to comparatively more activity of A. mellifera on radish bloom during this year. The present studies suggest that A. cerana along with other natural pollinators are providing natural pollination services for pollination of radish and other crops. Hence there is urgent need to devise suitable strategies for the conservation of these pollinators.